(18)F-FDG-PET/CT for the detection of disease in patients with head and neck cancer treated with radiotherapy - Helsen, Nils (PLoS One, 2017)
OBJECTIVE: The aim of this study is to evaluate the diagnostic performance of FDG-PET/CT for the detection of residual disease after (chemo)radiotherapy in patients with head and neck squamous cell carcinoma (HNSCC) and to evaluate the prognostic value of the FDG-PET/CT findings. METHODS: Patients with HNSCC who underwent FDG-PET/CT after (chemo)radiotherapy were studied retrospectively. RESULTS: 104 FDG-PET/CT-scans were performed at a median of 13.2 weeks post-treatment (5.4–19.0 weeks). The diagnostic performance was time dependent with decreasing sensitivity and slightly increasing specificity over time. Sensitivity, specificity, PPV and NPV at 9 months after imaging were 91%, 87%, 77% and 95%, respectively. In a logistic regression model, the odds of a correct FDG-PET/CT increased with 33% every additional week after end of therapy (p = 0.01) and accuracy plateaued after 11 weeks (97%; p<0.001). A complete response on FDG-PET/CT was associated with an overall survival benefit (50.7 versus 10.3 months; p<0.001). Residual disease on FDG-PET/CT increased the risk of death 8-fold (p<0.001). CONCLUSION: FDG-PET/CT is able to detect residual disease after (chemo)radiotherapy, with an optimal time point for scanning between 11–12 weeks after therapy. However, a reevaluation is probably necessary 10–12 months after the FDG-PET/CT to detect late recurrences. In addition, FDG-PET/CT can guide decisions about neck dissection and identifies patients with poor prognosis.